A Combination Treatment of Raloxifene and Vitamin D Enhances Bone-to-Tendon Healing of the Rotator Cuff in a Rat Model. Issue 9 (July 2020) - Kim, Dong Min; Shim, In Kyoung; Shin, Myung Jin; Choi, Jae Hee; Lee, Yu Na; Jeon, In-Ho; Kim, Hyojune; Park, Dongjun; Kholinne, Erica; Koh, Kyoung-Hwan
Background: Tearing and degeneration of the rotator cuff at the tendon-to-bone junction are common in adults aged ≥50 years. Few studies have reported on the relationship between estrogen and the rotator cuff enthesis. In addition to preventing bone loss, selective estrogen receptor modulators have been shown to improve tendon and muscle quality. Purpose: To evaluate the effects of raloxifene (RLX) and vitamin D on rotator cuff tendon-to-bone healing in a rat model. Study Design: Controlled laboratory study. Methods: A total of 29 female rats (58 shoulders) were assigned to 4 groups: (1) control group, (2) ovariectomy (OVX)–only group, (3) no RLX group (OVX and rotator cuff repair [RCR]), and (4) RLX group (OVX, RCR, and RLX). Rats that did not undergo rotator cuff tear (RCT) surgery were divided into the control and OVX-only groups according to OVX surgery. Rats that underwent RCT surgery and RCR were divided into the no RLX and RLX groups according to RLX and vitamin D administration. An estrogen-deficient state was induced by OVX at 12 weeks of age. Bone mineral density (BMD) and trabecular bone characteristics were measured by micro–computed tomography, and healing of the tendon-to-bone junction was evaluated by biomechanical testing, histomorphometry, and micro–magnetic resonance imaging (MRI). Results: The mean final body weight (BW; 461.6 ± 47.3 g) of the OVX-only group was significantly higher and BMD (0.25 ± 0.07 g/cm 3 ) was significantly lower ( P < .001) than the mean final BW (338.5 ± 35.1 g) and BMD (0.48 ± 0.05 g/cm 3 ) of the control group. In contrast, the RLX group showed that the BW (369.6 ± 35.8 g) and BMD (0.41 ± 0.08 g/cm 3 ) were not significantly different from the control group. The RLX group had a significantly higher histomorphometric total score (8.50 ± 1.05) than the no RLX group (4.83 ± 2.48). On biomechanical testing, the RLX group (29.7 ± 9.1 N) showed a significantly higher load to failure than the no RLX group (19.4 ± 8.8 N). On micro-MRI, the RLX group had a more homogeneous low signal and tendon continuity than the no RLX group. Conclusion: The combination treatment of RLX and vitamin D prevented a decrease in local BMD (greater tuberosity of the proximal humerus) and enhanced tendon-to-bone healing of the rotator cuff in a rat model. Clinical Relevance: This study induced an estrogen-deficient state similar to the human postmenopausal state and used drugs that are actually being prescribed in a clinical situation.